Person-centered maternity care and its associated factors during childbirth at selected public hospitals in Eastern Ethiopia: a cross-sectional study - Gebreyesus, Arsema; Semahegn, Agumasie; Tebeje, Fikru; Lonsako, Arega Abebe; Girma, Sagni (Frontiers in Global Women's Health, 2025)
BackgroundMaternal mortality has remained a major public health issue globally. Although there has been substantial reduction in maternal mortality, Ethiopia is still one of the highest burden countries in sub-Saharan Africa. Person-centered maternity care plays a key role in ending preventable maternal mortality. Nevertheless, little is known about the status of person-centered maternity care during facility-based childbirth in eastern Ethiopia. Therefore, the aim of this study was to assess the status of person-centered maternity care and its associated factors during childbirth at selected public hospitals in eastern Ethiopia.MethodsWe had conducted a facility-based cross-sectional study at selected public hospitals in eastern Ethiopia from May 16 to June 17, 2022. A total of 420 postpartum women, selected by a systematic random sampling technique, were included in the study. We had collected our data by face-to-face interview using a pretested structured questionnaire. Then, the data were entered into EpiData 4.6 and exported to SPSS version 26 for cleaning and analysis. We applied linear regression analyses to determine the associations between dependent and independent variables. The association was reported using a β coefficient with a 95% confidence interval (CI) and a p-value ≤0.05.ResultsThe percentage mean score of person-centered maternity care was 68.1 (CI: 59.94, 62.66), SD (±14.1). From the subscales of person-centered maternity care, the percentage mean score of dignity and respect was 80.6%, communication and autonomy 61.1%, and 67.3% for supportive care. Women who'd had antenatal care (ANC) follow-up (β = 5.66, 95% CI: 2.79, 8.53) and women who gave birth to a live newborn (β = 7.59, 95% CI: 3.97, 11.20) had a positive association with person-centered maternity care. However, women who had experienced childbirth complications (β = −7.01, 95% CI: −9.88, −4.13) and those who had a hospital stay of more than two days (β = −4.08, 95% CI: −6.79, −1.38) were negatively associated with person-centered maternity care.ConclusionOur study revealed that the mean person-centered maternity care score of the participants was significantly higher than in previous studies. Women who had antenatal care follow-up, experienced complications during childbirth, gave birth to a live newborn, and had a hospital stay of more than two days were significantly associated with person-centered maternity care. Therefore, we strongly concluded that strengthening antenatal care utilization and early detection and appropriate management of childbirth and pregnancy complications would greatly improve person-centered maternity care.